PROCESS AS A TRANSITIVITY ELEMENT IN CLASSROOM DISCOURSE - Yuniar Yuniar; T. Silvana Sinar; Busmin Gurning (Universitas Negeri Medan, 2018)
The purposes of the study is to describe about the experiential realization through transitivity analysis in classroom discourse, and only concerns with one component of the metafunctions that is the experiential meaning. The problem investigated in this study are (1) The transitivity processes used by the teachers in English classroom context; (2) the description of processes realized by teachers in the classroom context; and (3) the field of discourse in which the processes are realized in the classroom context. This study is data -based with descriptive qualitative and quantitative in nature and the method is observational. The location of the sudy were in 2 schools,and the subjects of the study are 3 English teachers from both schools in Aceh tamiang 2016. In collecting the data, this study is used a means of audio-visual recording and transcriptions, and analyzed by employing Interactive Model. The result of the study from data analysis with total of clauses produced by 3 teachers each two sessions are 2175 clauses. It gained 726 clauses of Material Process (33.38%), followed by behavioural process gained 425 clauses (19.54%), relational process gained 296 clauses (13.60%), existantial process gained 287 clauses (13.19%), mental process gained 250 clauses (11.49 %), and verbal process gained 191 clauses (8.78 %).Keywords: Classroom Discourse, Process of Transitivity, Systemic Functional Linguistic